2017
DOI: 10.1177/2379298117736885
|View full text |Cite
|
Sign up to set email alerts
|

An Andragogical Approach to Teaching Leadership

Abstract: Students in today’s college classroom are diverse in age and work, leadership, and life experiences; hence, students transitioning into adulthood may understand and relate core leadership knowledge to their own experiences differently than mature adults. As such, we call upon andragogy, a theory of adult learning, to inform our approach to teaching leadership. We employ andragogy and its six assumptions (the learners’ self-concept, the role of experience, readiness to learn, orientation to learning, motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…Huggins, Lesseig, and Rhodes [35] found that when early career teachers of mathematics were given intentional opportunities to reflect on their personal journey through these levels of leadership, they recognized this as an individual experience with their unique timetable for internalizing their leadership capabilities. Furthermore, McCauley et al [36], advocate for using a portfolio of leadership experiences in order to have opportunities for teachers seeking to grow in an instructional leadership role to recognize their progress. This portfolio would be organized based on the assumptions of andragogy as described by Knowles and predecessors [19,20,36] in order for emerging instructional leaders to further develop their skills.…”
Section: Preparing Mathematical Instructional Leadersmentioning
confidence: 99%
See 1 more Smart Citation
“…Huggins, Lesseig, and Rhodes [35] found that when early career teachers of mathematics were given intentional opportunities to reflect on their personal journey through these levels of leadership, they recognized this as an individual experience with their unique timetable for internalizing their leadership capabilities. Furthermore, McCauley et al [36], advocate for using a portfolio of leadership experiences in order to have opportunities for teachers seeking to grow in an instructional leadership role to recognize their progress. This portfolio would be organized based on the assumptions of andragogy as described by Knowles and predecessors [19,20,36] in order for emerging instructional leaders to further develop their skills.…”
Section: Preparing Mathematical Instructional Leadersmentioning
confidence: 99%
“…Furthermore, McCauley et al [36], advocate for using a portfolio of leadership experiences in order to have opportunities for teachers seeking to grow in an instructional leadership role to recognize their progress. This portfolio would be organized based on the assumptions of andragogy as described by Knowles and predecessors [19,20,36] in order for emerging instructional leaders to further develop their skills. This practice would provide a scaffold for becoming aware of not only one's growth in leadership skills but also in allowing oneself to better understand the environment that also contributes to the progress towards increasing both self-efficacy as well as skills in instructional leadership.…”
Section: Preparing Mathematical Instructional Leadersmentioning
confidence: 99%
“…Though there are examples of andragogical principles being applied in management education (McCauley et al, 2017), such examples seem to be lacking in organizational training, especially for low-skilled occupations. Knowles et al (2012) provided a case example of a workplace literacy programme for those lacking in basic literacy skills, though they do not give detail of how andragogical principles were applied to the design of the programme.…”
Section: Sdt and Autonomy-supportive Style Trainingmentioning
confidence: 99%
“…Though there are examples of andragogical principles being applied in management education (McCauley et al , 2017), such examples seem to be lacking in organisational training, especially for low-skilled occupations. Knowles et al .…”
Section: Introductionmentioning
confidence: 99%
“…curricula to develop students' business communication skills, in particular, their ability to learn and work in teams, both on-site and online modalities. This is embedded in an andragogical approach to adult education (Loeng, 2018;McCauley et al, 2017;McGrath, 2009) and has resulted in the graduates' gainful employment, more successful careers and promotion, better work/life balance.…”
Section: Introductionmentioning
confidence: 99%